CURRENT RECOMMENDATIONS ON RISK STRATIFICATION AND SUDDEN CARDIAC DEATH PREVENTION IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY (BASED ON THE 2011 RECOMMENDATIONS BY THE AMERICAN COLLEGE OF CARDIOLOGY / AMERICAN HEART ASSOCIATION) - E. V. Privalova; V. Yu. Kaplunova; N. V. Khabarova; G. A. Shakaryants; Yu. N. Belenkov (Кардиоваскулярная терапия и профилактика)
One of the clinical scenarios of hypertrophic cardiomyopathy (HCMP) is sudden cardiac death (SCD). The stratification of SCD risk is the key component of defining the therapeutic strategy in HCMP patients. Timely preventive treatment is the only life-saving intervention in patients with high SCD risk. The available clinical evidence suggests that SCD risk stratification is an effective algorithm for determining the need for preventive treatment. The latter should be individualised, based on the risk levels in each patient.